2023
DOI: 10.3390/brainsci13060957
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time for a Paradigm Shift in the Treatment of Schizophrenia? The Use of Inflammation-Reducing and Neuroprotective Drugs—A Review

Abstract: Comprehending the pathogenesis of schizophrenia represents a challenge for global mental health. To date, although it is evident that alterations in dopaminergic, serotonergic, and glutamatergic neurotransmission underlie the clinical expressiveness of the disease, neuronal disconnections represent only an epiphenomenon. In recent years, several clinical studies have converged on the hypothesis of microglia hyperactivation and a consequent neuroinflammatory state as a pathogenic substrate of schizophrenia. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 123 publications
1
6
0
Order By: Relevance
“…Interestingly, other anti-inflammatory medications, such as celecoxib, davunetide, dextromethorphan, fatty acids, pregnenolone, statins, and varenicline, did not have a significant impact on SCZ symptoms in a recent meta-analysis, highlighting the presence of inflammatory-pathway-specific abnormalities in SCZ development. Collectively, these findings support the emerging importance of immune-related dysfunction as a targetable pathology of SCZ [ 196 ]. However, additional trials are required to confirm these findings as the effectiveness of selected therapies, including anti-IL-6 and anti-CD20 antibodies as well as prednisolone, has been questioned in some clinical studies [ 197 , 198 , 199 ].…”
Section: Implications For Mechanistic Studies and Therapeutic Develop...supporting
confidence: 69%
“…Interestingly, other anti-inflammatory medications, such as celecoxib, davunetide, dextromethorphan, fatty acids, pregnenolone, statins, and varenicline, did not have a significant impact on SCZ symptoms in a recent meta-analysis, highlighting the presence of inflammatory-pathway-specific abnormalities in SCZ development. Collectively, these findings support the emerging importance of immune-related dysfunction as a targetable pathology of SCZ [ 196 ]. However, additional trials are required to confirm these findings as the effectiveness of selected therapies, including anti-IL-6 and anti-CD20 antibodies as well as prednisolone, has been questioned in some clinical studies [ 197 , 198 , 199 ].…”
Section: Implications For Mechanistic Studies and Therapeutic Develop...supporting
confidence: 69%
“…Early detection and prompt treatment of catatonic symptoms is critical to avoid chronicity [53]. Thus, psychosocial interventions, cognitive remediation, and pharmacological approaches, purposeful to treat the negative symptoms and underlying in ammation could help to nd an answer to unmet needs still in the treatment of schizophrenia [7,54].…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline is a pharmacological agent with antibacterial characteristics and the ability to reduce inflammation. Several clinical investigations have shown that the adjunctive use of minocycline with antipsychotic therapies may enhance symptomatology in individuals with schizophrenia [ 56 ]. Six randomized controlled trials (RCTs) were selected for inclusion in a review.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, psychosocial interventions, cognitive remediation, clinical and pharmacological approaches, purposeful to treat the negative symptoms and underlying inflammation could help to find an answer to unmet needs still in the treatment of schizophrenia [ 7 , 56 ].…”
Section: Discussionmentioning
confidence: 99%